SELF CARE DALAM PERSPEKTIF HADIS TEMATIK - Attoriq Islami Pasha; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
This study explores the concept of self-care from the perspective of Prophetic traditions (ḥadīth) using the thematic (mawḍū‘ī) approach. The research is motivated by the growing awareness of mental health and life balance in modern society, which is often challenged by social pressure and a fast-paced lifestyle. Through an analytical study of various ḥadīths related to physical, emotional, social, spiritual, and intellectual self-care, the research finds that Islam provides a comprehensive framework for personal well-being as an act of worship and moral responsibility. Prophet Muhammad ﷺ emphasized the importance of balance between worship and rest, patience and gratitude, as well as cleanliness and health as foundations of a harmonious life. Therefore, self-care in Islam is not merely an individual practice but an integral aspect of sustaining spiritual well-being, productivity, and social harmony